Persepsi dan Motivasi Mahasiswa Terhadap Pembelajaran Sinkron Maya Statistika dan Analisis Data: Penelitian - Ismadi Sihombing; Sarma Dewi Kemala S (Jurnal Pustaka Cendekia Pendidikan, 2026)
Digital transformation in higher education has reshaped the teaching of quantitative courses that demand high precision, such as Statistics and Data Analysis. This study evaluates students' perceived ease of use, perceived usefulness, and motivation in synchronous virtual learning using Microsoft Teams. A quantitative descriptive method was used with a validated and reliable Likert-scale questionnaire distributed online via Google Forms to 65 students of the Information Systems Study Program (Morning and Evening Class A). The results show that 78.8% of students stated that synchronous virtual learning made it easier to understand the material, 81.6% held a positive perception, and 85.7% showed a high level of learning motivation. Spearman rank correlation showed that perceived ease of use and usefulness were significantly and positively associated with learning motivation. The study highlights that specific Teams features (high-resolution screen sharing and cloud recording) positively affected students' technical understanding of statistical software (SPSS or Excel). The study concludes that synchronous virtual technology is effective when combined with interactive pedagogical strategies.